2019
DOI: 10.1104/pp.19.00792
|View full text |Cite
|
Sign up to set email alerts
|

NatB-Mediated N-Terminal Acetylation Affects Growth and Biotic Stress Responses

Abstract: Short title: NatB acetylates 20% of the proteome in Arabidopsis NatB-mediated N-terminal acetylation affects growth and abiotic stress responses One-sentence Summary: Initiator methionine acetylation by NatB is evolutionary conserved and critical for abiotic stress responses in Arabidopsis thaliana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 60 publications
4
76
0
Order By: Relevance
“…Gene expression analysis confirmed that knockdown of NAA50 results in an up-regulation of defense signaling. These results are consistent with the observation that loss of NAA50 results in an accumulation of stress response proteins (Armbruster et al, 2020).…”
Section: Naa50 Is Required For Growth and The Suppression Of Stress Rsupporting
confidence: 92%
See 3 more Smart Citations
“…Gene expression analysis confirmed that knockdown of NAA50 results in an up-regulation of defense signaling. These results are consistent with the observation that loss of NAA50 results in an accumulation of stress response proteins (Armbruster et al, 2020).…”
Section: Naa50 Is Required For Growth and The Suppression Of Stress Rsupporting
confidence: 92%
“…To investigate the role of NAA50 in plants, we characterized two T-DNA insertion mutants (SAIL_1210_A02 and SAIL_1186_A03), which we designated naa50-1 and naa50-2, respectively. The naa50-1 mutant contains a T-DNA insertion in intron 2, while naa50-2 contains a T-DNA insertion in intron 1, and neither produces detectable full-length transcript or NAA50 protein (Armbruster et al, 2020). We confirmed the presence of homozygous T-DNA insertions in NAA50 in each line using PCR-based genotyping (see "Materials and Methods").…”
Section: Arabidopsis Naa50 Is Highly Conserved and Essential For Devementioning
confidence: 72%
See 2 more Smart Citations
“…However, hNAA20 and hNAA25 share only ~40% and ~20% sequence identity with the Candida albicans homologue [57], respectively. Moreover, nearly all biological studies of NatB have been conducted in Saccharomyces cerevisiae [58][59][60], Arabidopsis [61,62], mouse [63] and human [17,[43][44][45] as model organisms. As a result, the mode of human NatB-mediated catalysis and aSyn-specific NatB recognition remains unresolved.…”
Section: Introductionmentioning
confidence: 99%